Conceptual design of a leg-wheel chassis for rescue operations. (1st December 2017) - Janos, Rudolf; Sukop, Marek; Semjon, Jan; Vagas, Marek; Galajdova, Alena; Tuleja, Peter; Koukolová, Lucia; Marcinko, Peter
The article describes the concept of a locomotive construction for a robot moving along an urbanized or unstructured natural terrain. The most suitable variant was the development of a hybrid leg-wheel chassis for a service robot. It has only been confirmed that the proposed design solution for the leg-wheel hybrid chassis can largely determine activities, requiring a high degree of mobility in different application environments and, at the same time, a high efficiency motion speed over a relatively flat terrain. The geometry for the middle robot service category was processed to verify mobility. The proposed geometry has been optimized for the obstacles defined by the rescuers' requirements. The result of the simulation is the mobility verification and the recommendation for the prototype development of the service robot.